2015
DOI: 10.2337/dc15-0753
|View full text |Cite
|
Sign up to set email alerts
|

Momentary Predictors of Insulin Restriction Among Adults With Type 1 Diabetes and Eating Disorder Symptomatology

Abstract: OBJECTIVEIndividuals with type 1 diabetes who restrict insulin to control weight are at high risk for diabetes-related complications and premature death. However, little is known about this behavior or how to effectively intervene. The aim of the current study was to identify predictors of insulin restriction in the natural environment that might inform new treatment directions.RESEARCH DESIGN AND METHODSEighty-three adults with type 1 diabetes and a range of eating disorder symptomatology completed 3 days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
70
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 37 publications
3
70
0
2
Order By: Relevance
“…The present study also builds on previous studies that have reported associations between more disordered eating behaviours and poorer psychosocial attributes in individuals with Type 1 diabetes [13,27,30]. In a sample of 199 adolescents with Type 1 diabetes, Grylli et al [27] found that young people with disordered eating behaviours had a less positive attitude toward life, more somatic complaints, lower self-esteem, and more depressive symptoms than young people without disordered eating behaviours.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The present study also builds on previous studies that have reported associations between more disordered eating behaviours and poorer psychosocial attributes in individuals with Type 1 diabetes [13,27,30]. In a sample of 199 adolescents with Type 1 diabetes, Grylli et al [27] found that young people with disordered eating behaviours had a less positive attitude toward life, more somatic complaints, lower self-esteem, and more depressive symptoms than young people without disordered eating behaviours.…”
Section: Discussionsupporting
confidence: 75%
“…The present study also builds on previous studies that have reported associations between more disordered eating behaviours and poorer psychosocial attributes in individuals with Type 1 diabetes . In a sample of 199 adolescents with Type 1 diabetes, Grylli et al .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The pattern of fear of weight gain leading to insulin omission, as well as insulin overdose after binge‐eating episodes are patterns which have been previously described , but the deeper‐seated motives behind the insulin manipulation that bloggers described, such as the ‘thrill’, ‘addictive’, ‘experimental’ or ‘secretive’ aspects of insulin omission were novel observations. Preliminary evidence has found highly processed foods share pharmacokinetic properties with addictive drugs .…”
Section: Discussionmentioning
confidence: 72%